QUALITY OF CROP YIELD IN THE EUROPEAN TERRITORY OF THE RUSSIAN FEDERATION UNDER THE CONDITIONS OF CLIMATE CHANGE - L. Y. Novikova; S. N. Travina; T. E. Zhigadlo; L. G. Naumova; E. V. Zuev (Труды по прикладной ботанике, генетике и селекции)
The positive trend of starch content in potato tubers under the conditions of Murmansk Province and sugar content in grapes under the conditions of Rostov Province is shown for the period of the 1990s. Weather dependence of protein content in wheat was investigated in the experiments of 1963-1993 at four experimental stations of the Vavilov Institute. Direct dependence of the studied quality indicators on the sum of temperatures above 15°C and inverse dependence on the sum of rainfall for this period have been identified.